2007
DOI: 10.1074/jbc.m611768200
|View full text |Cite
|
Sign up to set email alerts
|

Human TRBP and PACT Directly Interact with Each Other and Associate with Dicer to Facilitate the Production of Small Interfering RNA

Abstract: Mammalian Dicer interacts with double-stranded RNA-binding protein TRBP or PACT to mediate RNA interference and micro-RNA processing. TRBP and PACT are structurally related but exert opposite regulatory activities on PKR. It is not understood whether TRBP and PACT are simultaneously required for Dicer. Here we show that TRBP directly interacts with PACT in vitro and in mammalian cells. TRBP and PACT form a triple complex with Dicer and facilitate the production of small interfering RNA (siRNA) by Dicer. Knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(239 citation statements)
references
References 48 publications
(57 reference statements)
10
219
0
3
Order By: Relevance
“…The accumulation of mature miRNAs in vivo and the efficiency of siRNA-induced RNAi are affected upon depletion of PACT (74). These findings were confirmed in shRNA-induced RNAi, but not when using siRNAs, suggesting that TRBP and PACT function primarily in siRNA production (75). Moreover, the presence of both TRBP and PACT increased the ability of Dicer to cleave a 566-bp long dsRNA in vitro, as compared to TRBP and PACT added individually (75).…”
Section: Pkr-activating Protein and The Pkr Signaling Pathwaysupporting
confidence: 65%
See 1 more Smart Citation
“…The accumulation of mature miRNAs in vivo and the efficiency of siRNA-induced RNAi are affected upon depletion of PACT (74). These findings were confirmed in shRNA-induced RNAi, but not when using siRNAs, suggesting that TRBP and PACT function primarily in siRNA production (75). Moreover, the presence of both TRBP and PACT increased the ability of Dicer to cleave a 566-bp long dsRNA in vitro, as compared to TRBP and PACT added individually (75).…”
Section: Pkr-activating Protein and The Pkr Signaling Pathwaysupporting
confidence: 65%
“…The C-terminal domain of PACT can also mediate homomultimerization (79). Interestingly, a recent study demonstrated that PACT directly interacts with TRBP and that this complex associates with Dicer to facilitate production of siRNAs (75).…”
Section: Pkr-activating Protein and The Pkr Signaling Pathwaymentioning
confidence: 99%
“…11,13 Moreover, two factors TRBP and PACT shown to be important in mammalian RNAi were in fact first described to have IFN effector functions. [44][45][46][47] Recent evidence indicates that the IFN's antiviral activity is mediated by the miRNA arm of the RNAi pathway. 48 Overall, these overlaps suggest that the IFN system and RNAi pathway may act cooperatively to control virus infection.…”
Section: Increased Virus Replication In Mammalian Cellsmentioning
confidence: 99%
“…In fact, PACT can bind directly to TRBP and form a ternary complex with Dicer and TRBP to facilitate the production of siRNAs by Dicer. Knockdown of both TRBP and PACT in cultured mammalian cells led to a significant inhibition of gene silencing mediated by shRNAs, but not by siRNAs, suggesting that TRBP and PACT function primarily at the step of siRNA production (97). Despite exerting opposite effects on PKR, PACT and TRBP may thus play a similar, possibly redundant, role in miRNA biogenesis and function.…”
Section: Trbp and Pact Function In Rna Silencingmentioning
confidence: 97%